Lycopene Maintains Mitochondrial Homeostasis to Counteract the Enterotoxicity of Deoxynivalenol - Zihui Cai; Fengjuan Chen; Youshuang Wang; Xuebing Wang; Xu Yang; Cong Zhang (MDPI AG, 2023)
The intestinal tract is a target organ for Deoxynivalenol (DON) absorption and toxicity. Mitochondrial homeostasis imbalance is the gut toxicity mechanism of DON. Lycopene (LYC) has intestinal protective effects and can maintain mitochondrial homeostasis in response to various danger signals. The purpose of this study was to explore the protective effect of LYC on DON-induced IPEC-J2 cells damage. These results showed that DON exposure induced an increase in the levels of malondialdehyde and reactive oxygen species (ROS) in IPEC-J2 cells. DON impaired IPEC-J2 cell barrier function and caused mitochondrial dysfunction by inducing mitochondrial permeability transition pore (MPTP) opening, mitochondrial membrane potential (MMP) reducing, destroying mitochondrial fission factors, mitochondrial fusion factors, and mitophagy factors expression. However, adding LYC can reduce the toxic effects of DON-induced IPEC-J2 cells and decrease cellular oxidative stress, functional damage, mitochondrial dynamics imbalance, and mitophagy processes. In conclusion, LYC maintains mitochondrial homeostasis to counteract the IPEC-J2 cells' toxicity of DON.